Synchronous gynecologic malignancy and preliminary results of Lynch syndrome - Kim, Min Kyu (Korean Society of Gynecologic Oncology and Colposcopy, 2011)
OBJECTIVE: Lynch syndrome is a hereditary cancer syndrome that increases the risks of colorectal and gynecologic malignancies such as endometrial and ovarian cancer. Studies have shown that mutations in mismatch repair genes (MSH2, MSH6, and MLH1) are associated with Lynch syndrome. The aim of our study was to estimate the value of MSH2, MSH6, and MLH1 immunohistochemistry based on family history in a Korean sample. METHODS: Thirty six women with synchronous gynecologic tumors of endometrial and ovarian cancer were identified among patients being treated at our institution. Among them, 32 patients had tumor blocks (total 62 slides) available for analysis. According to a diagnostic algorithm, we performed immunohistochemistry analyses. Staining was scored based on intensity and proportion (negative or 0: intensity undetectable or minimal, proportion <5%; weak or 1+: intensity mild, proportion 5-30%; strong or 2+: intensity moderate to marked, proportion 30-99%). RESULTS: Among 32 eligible patients, 9 (28%) had a family history of cancer. Six patients (19%) were negative for MLH1; among them, four (4/6) were negative at both sites. Nine patients (28%) were negative for MSH2 or MSH6 at both sites or negative for both MSH2 and MSH6. Among these three patients showed negative staining for both sites. The three patients showing negative staining for MLH1, MSH2, and MSH6 at both sites with family history were considered to be the screening positive groups of Lynch syndrome. CONCLUSION: In this study, the frequency of Lynch syndrome associated immunohistochemical staining (MLH1, MSH2, and MSH6) group was estimated as 9% (3/32) among Korean women with synchronous gynecologic tumors.